PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR KELAS XII N 1 SIPAHUTAR T.P 2019/ 2020 - Parapat, Nicholas (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
AbstracThis research aims to determine the influence of the use of audio visual media on the outcome of PAK grade XII students SMA Negeri 1 Sipahutar learning year 2019/2020. The research hypothesis is that there is a positive and significant influence on the use of audio visual media on the outcome of PAK grade XII students SMA Negeri 1 Sipahutar Year learning 2019/2020.This research is a correlational study using the descriptive and inferential statistical techniques. The population is the entire grade XII student of SMA Negeri 1 at the 2019/2020 Christian Protestant learning year, amounting to 358 people. Sampling using the Random Sampling technique of 12% of the population is 40 people. This research instrument is a closed poll for variable X and test for variable Y. This research is a correlational study using the descriptive and inferential statistical techniques. The population is the entire grade XII student of SMA Negeri 1 at the 2019/2020 Christian Protestant learning year, amounting to 358 people. Sampling using the Random Sampling technique of 12% of the population is 40 people. This research instrument is a closed poll for variable X and test for variable YKeywords: Penggunaan Media Audio Visual, Hasil Belajar Siswa.